In-Hospital Evolution of Non Operated Aneurysmal Subarachnoid Hemorrhage at the Neurology Unit of Befelatanana University Teaching Hospital, Antananarivo - Glorien, Lemahafaka Jemissair; Finiavana, Rasaholiarison Nomena; Andriamasinavalona, Rajaonarison Lala; Julien, Razafimahefa; Noel, Zodaly; Djacoba, Tehindrazanarivelo Alain (European Scientific Journal, ESJ, 2018)
Subarachnoid hemorrhage is defined as a sudden irruption of blood in subarachnoid spaces. This study aims to determine the profile and in-hospital evolution of patients with post aneurysmal subarachnoid hemorrhage, who did not have surgical treatment in the Neurology Unit of Befelatanana University Hospital, Antananarivo, Madagascar. This study was a descriptive retrospective study within a period of 4 years, from January 1st, 2014 to December 31th, 2017. The study was carried out in hospitalized patients for subarachnoid hemorrhage with aneurysmal origin. We included 52 patients, with an average age of 48 years and a female predominance. They are housewives in majority of cases. 52% of the cases live in urban areas while 77% of cases have high blood pressure. The main clinical manifestation was a sudden headache, and intracranial aneurysm was located at the anterior communicating artery in 52% of cases. All patients benefited from drug treatments in majority of cases. Due to the lack of financial means, 60% had neurological complications. However, in-hospital mortality rate was at 13%. This study helps us to suggest to our patients medical treatment of their subarachnoid hemorrhage during hospitalization because of difficult access to surgery. It also aims to propose surgery outside the acute phase of the disease.